Strategi Peningkatan Ekspor Indonesia dalam Perdagangan Bebas - - Mastur (AKSES: Jurnal Ekonomi dan Bisnis, 2006)
The article explored Indonesian export development to anticipate the challenge of free trade. The Challenge were : export structure still base on traditional market and just on certain commodity, Indonesian non oil export also had many challenge from Others Asian Exporter state. The improvement on quantity and quality must be achieved with many strategy e g : export divert policy specially on non oil export both good or service,  improve the global competence product and promote of export function on catalyze economic growth